Climate Change and its Impact on Rice Yield - Rijal, Krishna Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Monsoon patterns have been changing noticeably in recent years around the globe. These changes have tremendous effects on agriculture systems especially in the areas where rainfall is the precondition of agriculture. This paper will investigate monsoon patterns in Nepal and how they correlate with recorded rice yields. The results were analyzed and cross-checked with AquaCrop, a crop water productivity model. The findings indicate that the Nepal’s monsoon patterns do not follow a definitive trend. Parameters such as onset and withdrawal dates, duration and distribution are quite unpredictable. The patterns, however, do have direct impact on national average rice yields, but that effect has turned less sensitive in recent years. The findings suggest that though monsoon has vital role on rice production in Nepal, where agriculture systems depend primarily on rainfall, more research is required to predict more accurately and precisely the production functions and relationships to yield. The better we understand this relationship, the more we can compensate for adverse monsoon patterns through anticipatory deployment of ag-technologies and advanced management options. Furthermore, support from legislators will be required to move these ideas into practice. DOI: http://dx.doi.org/10.3126/hn.v16i0.12215 HYDRO Nepal Journal of Water Energy and Environment Issue. 16, 2015, January Page: 23-27 Upload date: March 1, 2015